The Influence of Brand Trust and Religiosity on The Mudharabah Deposit Product Selection Decision - Prianda Pebri; Surya Bakti (Syntax Corporation Indonesia, 2022)
The purpose of this study is to analyze the influence of brand trust and religiosity on the decision to choose mudharabah deposit products in Islamic Commercial Banks. Population and sample are 100 respondents selected by accidental sampling in order to obtain research data through filling out a questionnaire. The results showed that partially or simultaneously the two independent variables consisting of brand trust and religiosity have a positive and significant effect on the decision to choose mudharabah deposit products in Islamic Commercial Banks.